ANALISIS FAKTOR YANG MEMPENGARUHI KINERJA PERANGKAT DESA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi Kasus di Desa Tambak Ukir, Desa Kendit dan Desa Bugeman Kecamatan Kendit Kabupaten Situbondo) - Nurhalizah, Syindi; Ediyanto, Ediyanto; Ciptasari, Ayu Dita Windra (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
The village office is a building or room used as the center for administrative functions at the village level. It serves as a meeting place for village government officials, including the village head, village administration staff, and various departments or units related to public services and the interests of the village community. This research aims to analyze the factors affecting the performance of village officials with job satisfaction as an intervening variable (a case study in Tambak Ukir Village, Kendit Village, and Bugeman Village in the Kendit District of Situbondo Regency). The population for this study consists of all village officials from Tambak Ukir, Kendit, and Bugeman, totaling 41 individuals. The sampling technique used is purposive sampling. Data analysis and hypothesis testing in this study employ Partial Least Squares – Structural Equation Modeling (PLS-SEM). The results of the direct effect hypothesis test using Smart PLS 3.0 show that the Work Commitment variable has a positive and significant effect on Job Satisfaction, Work Ability has a positive but not significant effect on Job Satisfaction, Work Environment has a positive and significant effect on Job Satisfaction, Work Commitment has a positive but not significant effect on Employee Performance, Work Ability has a positive but not significant effect on Employee Performance, Work Environment has a positive and significant effect on Employee Performance, and Job Satisfaction has a positive and significant effect on Employee Performance. The results of the indirect effect hypothesis test indicate that Work Commitment has a positive but not significant effect on Employee Performance through Job Satisfaction, Work Ability has a positive but not significant effect on Employee Performance through Job Satisfaction, and Work Environment has a positive but not significant effect on Employee Performance through Job Satisfaction.